Características vocais e propriocepção do envelhecimento, queixa e saúde vocal em mulheres idosas de diferentes faixas etárias - Paes, Marília Bentes (2008)
Introduction: There has been a worldwide demographic transition, characterized by a significant population increase in the specific age group of those who are 60 years old or older. This fact has brought an increasing concern towards elderly citizens. In this manner it is very important to carry on researches with different age groups of this particular population segment, since grouping these people simply as elders may conceal the bio-psychosocial differences existing amongst them. The subjects of this study were exclusively women. This option was made because they are the greater part of the elderly population and more frequently seek help at health units. Aim: To compare the vocal characteristics, awareness of aging, vocal complaints and vocal health of women between 60 and 90 years of age. Method: The subjects of this study were 94 elderly women, distributed in three groups: G1 (ages 60- 69), G2 (ages 70-79) and G3 (ages 80-90). A form consisting of questions on occupational aspects, everyday habits, vocal health, vocal and auditory aspects and perceptions about the aging process was filled out. Maximum phonation times of vowel /a/ and phonemes /s/ and /z/ were measured. A voice recording which registered spontaneous conversation of the subjects was also performed. Three speech therapists specialized in the voice field perceptually evaluated the recorded voices. The collected data was analyzed descriptively, and then statistical analysis was performed to compare the different age groups. Results: There was a statistically significant association between age group and vocal demand, reported difficulties to sing, reported hearing difficulties, use of hearing aids, respiratoryspeech coordination, articulation of speech and vocal quality. Although there was no statistically significant correlation between the following issues, there was a percentage increase along the age groups in other parameters: number of illnesses per person; phlegm complaints; complaints of hearing but not understanding; tinnitus complaints; reports of hearing impairments; use of hearing aids; watching television in high volumes; occurrence of low voice resonance; and awareness of vocal changes. As for the subjec aging process, there was a predominance of references to physiological aspects and of the daily activities in the answers provided by G1 (62.5%) and by G2 (52.9%), and of emotional aspects in the answers given by G3 (53.6%). The following issues were more prevalent in answers of certain age groups: health, prejudice, social isolation and the importance of practicing physical activities, mainly in G1; sadness and loneliness in G2; tiredness, lack of physical wellness, despondency and changes in social relationships, primarily in G3. Conclusion: The comparison of women of ages 60-69, 70-79 and 80-90 leads to the conclusion that there are significant differences between age groups related to vocal demands, reported difficulties in singing, respiratory-speech coordination, articulation of speech, vocal quality, reported hearing impairments, and use of hearing aids. The physiologic and daily life aspects mainly present in the answers of G1 and G2 as well as the emotional aspects predominant of the answers in G3 are factors that affect the way these women look at aging in general, and how they feel towards their own aging process. This study enables us to reaffirm the bio-psychosocial nature of the aging process, which is different not only from one person to another, but also in each age group